THE FIXITY POINT OF A LONG ELASTIC PILE ON COHESIONLESS SOIL FOR THE CALCULATION OF LATERAL BEARING CAPACITY - Dwi Maya Ermina Sari (Jurnal Teknologi Berkelanjutan, 2015)
Based on Broms method, for the simple calculation, lateral bearing capacity (Hu) depends on the ultimit moment of pile (Mu), shear strength (cu), pile dimensions (diameter D and depth L), and the depth of the fixity point. For practical reasons, the fixity pointis usually just assumed. This parameter is so important for the calculation of the lateral bearing capacity and the deflection of a pile. For that reason, it is necessary to carry out further research to determine the value of the fixity point.In this research, the fixity point is established by several approaches, namely modeling in laboratory, simulation using finite element, and theoretical calculation of Prasad and Chariand alsomethod by The American Concrete Institute (ACI). In this research, the fixity point affected by several parameters, that is diameter (D), depth (L) and pile eccentricity (e).